TI_GERICHTE 12.2018.156 vom 14. Mai 2020 , Appalto - garanzia per difetti - notifica dei difetti - diritto di scelta - TI Tribunale d'appello (2020)
Appalto - garanzia per difetti - notifica dei difetti - diritto di scelta